Snail and millipede complementarity in decomposing Mediterranean forest leaf litter mixtures (Functional Ecology, 2010)
1. The projected increase in loss of biodiversity worldwide has prompted the need to understand the role that diversity plays in key ecosystem functions such as litter decomposition and nutrient cycling. Here we asked how two contrasting species of saprophagous macrofauna and four Mediterranean forest leaf litter species interactively affect decomposition in a 6-week microcosm study. 2. Litter mass loss and macrofauna relative consumption rates (RCR) were measured on treatments with freshly fallen or partially decomposed leaf litter of Alnus glutinosa, Fraxinus angustifolia, Pistacia terebinthus and Quercus ilex as single-species or mixtures in absence and presence of the gastropod, Pomatias elegans, the diplopod, Glomeris marginata, or both macrofauna species. 3. Macrofauna consumed all litter substrates except freshly fallen P. terebinthus as a single-species litter that was fatal to both animals, although its presence in litter mixtures increased overall RCR. Consumption was higher in partially decomposed than freshly fallen litter, and higher in litter mixtures than in single-species litter. Both litter state and mixing interacted significantly with macrofauna treatment where generally, RCR by P. elegans alone was inferior to that of G. marginata alone or in combination with P. elegans. 4. An overall positive complementarity effect on litter RCR between G. marginata and P. elegans was observed in freshly fallen litter. Particularly strong complementarity was observed in two mixtures of freshly fallen litter and also in one mixture of partially decomposed litter. 5. There were no non-additive effects of litter mixing on litter mass loss in the absence of animals, indicating no interactions among litter substrates during decomposition. However, in the presence of either G. marginata and/or P. elegans, positive and negative interactions among litter substrates occurred and were enhanced or reversed by the addition of the second macrofauna species. 6. We conclude that saprophagous macrofauna play a critical role in the decomposition dynamics of Mediterranean forest litter by interacting with each other and by driving interactions among litter substrates.